Law Enforcement against Illegal Gold Mining: Navigating Regulatory and Justice Dilemmas in Indonesia - Mustakim Mustakim; Dewi Iryani; Hartana Hartana (Fakultas Syariah IAIN Langsa, 2026)
Law Number 3 of 2020 shifted the mining licensing paradigm from decentralization to centralization, yet the reality on the ground shows an increase in Illegal Gold Mining (PETI) activities accompanied by environmental damage and socio-economic dilemmas for poor communities. This research offers novelty by integrating the analysis of licensing arrangements as a preventive instrument, the effectiveness of criminal law enforcement under Article 158 of the Mining Law, and procedural and substantive obstacles in the field simultaneously. The research method used is normative juridical with statutory and conceptual approaches, supported by primary data from limited interviews with law enforcement officers. The findings show that licensing centralization has not been effective in preventing PETI due to the undesignated People's Mining Areas, corrupt bureaucracy, and weak supervision. Criminal law enforcement faces obstacles such as limited investigators, difficulties in evidence gathering, and the presence of protecting officials. Officers experience a social dilemma as they must enforce the law amidst the reality of poor communities dependent on PETI. This study recommends bureaucratic reform, designation of People's Mining Areas, strengthening investigator capacity, and a progressive and just legal approach.